Pharmacokinetics of cefotaxime in dialysis patients - Andrassy, Konrad (Diagnostic microbiology and infectious disease, 1995)
A literature review was carried out to assess the effect of hemodialysis, hemofiltration, and continuous ambulatory peritoneal dialysis on the pharmacokinetics of cefotaxime, particularly in patients with severe renal impairment. It was concluded that the dosage of cefotaxime, adjusted for renal function, would require no further adjustment during peritoneal dialysis or hemofiltration.
Elektronische Reproduktion der Druck-Ausgabe 20. Januar 2000
Gesehen am 25.10.2023